Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Bank Rakyat Indonesia KC Mabes TNI Cilangkap - Hafizah, Aulya Nur; Marwansyah, Sofyan (CV Warnak Johanna Nusantara, 2026)
This study aims to determine the influence of motivation and work environment in the company PT Bank Rakyat Indonesia Branch Office of the TNI Headquarters in Cilangkap. The population used in this study were 50 employees of the company. The data collection technique used a Google Form questionnaire and data processing using SPSS 25 with a probability sampling method. Data testing was carried out by data analysis, classical assumption test, T test, F test, coefficient of determination and correlation (R-Square). The results of the study showed that partially work motivation (X1) did not have a significant effect on employee performance (Y) and had a calculated t value of 0.394 <t table 2.011 and a Sig value of 0.695> 0.05. Then the work environment variable (X2) partially has a significant effect on employee performance (Y) and has a calculated t value of 2.324 > t table 2.011 and a Sig value of 0.025 < 0.05. Furthermore, it is known that simultaneously the work motivation variable (X1) and the work environment (X2) have a significant effect on the employee performance variable (Y) with a calculated f value of 6.342 > f table 3.20 and a Sig value of 0.004 < 0.05. The multiple linear regression equation is Y = 19.539 + 0.059X1 + 0.209X2.